2012
DOI: 10.1016/j.jcms.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-related osteonecrosis of the jaws – Characteristics, risk factors, clinical features, localization and impact on oncological treatment

Abstract: The development of ONJ has a multi-factorial aetiology and the clinical presentation can vary markedly. ONJ cannot only impair the quality of life but also the treatment of the underlying disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
177
4
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(207 citation statements)
references
References 36 publications
12
177
4
14
Order By: Relevance
“…· Second and third stages: include patients with exposed bone of various extents with other concomitant symptoms and signs that are mainly a result of secondary infection of the necrotic bone. The symptoms may include increased tooth mobility, formation of sinus tracts, suppuration and traumatic ulceration of oral mucosa adjacent to exposed bone, mandibular fracture, and/or cervical lymphadenopathy 18) . In the past, many studies worldwide have reported the diagnosis of BRONJ.…”
Section: Discussionmentioning
confidence: 99%
“…· Second and third stages: include patients with exposed bone of various extents with other concomitant symptoms and signs that are mainly a result of secondary infection of the necrotic bone. The symptoms may include increased tooth mobility, formation of sinus tracts, suppuration and traumatic ulceration of oral mucosa adjacent to exposed bone, mandibular fracture, and/or cervical lymphadenopathy 18) . In the past, many studies worldwide have reported the diagnosis of BRONJ.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is important as long-lasting inhibition of bone resorption can lead to increased bone fragility and therefore, to fractures caused by an inability to replace old bone with new bone and to repair microcracks [98,99].…”
Section: Effect Of Bisphosphonates On the Mechanical Properties Of Bonementioning
confidence: 99%
“…Recent human studies have shown that alendronate actually increases vertebral and non-vertebral fractures [98]. Therefore, it is prudent to administer a dose that does not induce too great an inhibition of turnover.…”
Section: Effect Of Bisphosphonates On the Mechanical Properties Of Bonementioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors mainly include: injuries associated with treatment in dental surgery, use of mismatched prosthetic restorations, presence of bone exostosis, odontogenic inflammations, poor oral hygiene, coexisting diabetes, simultaneous chemotherapy and/or steroid treatment, malnutrition and smoking. [13][14][15] The route of BP administration has a great impact. The risk of BRONJ is greater for intravenous therapy (0.8-15%).…”
mentioning
confidence: 99%